Control of sleep-to-wake transitions via fast aminoacid and slow neuropeptide transmission - Mosqueiro, Thiago (New J Phys, 2014)
The Locus Coeruleus (LC) modulates cortical, subcortical, cerebellar, brainstem and spinal cord circuits and it expresses receptors for neuromodulators that operate in a time scale of several seconds. Evidences from anatomical, electrophysiological and optogenetic experiments have shown that LC neurons receive input from a group of neurons called Hypocretins (HCRTs) that release a neuropeptide called hypocretin. It is less known how these two groups of neurons can be coregulated using GABAergic neurons. Since the time scales of GABA(A) inhibition is several orders of magnitude faster than the hypocretin neuropeptide effect, we investigate the limits of circuit activity regulation using a realistic model of neurons. Our investigation shows that GABA(A) inhibition is insufficient to control the activity levels of the LCs. Despite slower forms of GABA(A) can in principle work, there is not much plausibility due to the low probability of the presence of slow GABA(A) and lack of robust stability at the maximum firing frequencies. The best possible control mechanism predicted by our modeling analysis is the presence of inhibitory neuropeptides that exert effects in a similar time scale as the hypocretin/orexin. Although the nature of these inhibitory neuropeptides has not been identified yet, it provides the most efficient mechanism in the modeling analysis. Finally, we present a reduced mean-field model that perfectly captures the dynamics and the phenomena generated by this circuit. This investigation shows that brain communication involving multiple time scales can be better controlled by employing orthogonal mechanisms of neural transmission to decrease interference between cognitive processes and hypothalamic functions.